A study of pulmonary function abnormalities in obese individuals - Vaishnav, Bhumika T.; Tonde, Tushar V. (International Journal of Research in Medical Sciences, 2020)
Background: Previous studies suggest that obese individuals are prone to pulmonary function abnormalities. The aim of this study was to evaluate pulmonary function tests in obese individuals and to relate pulmonary abnormalities if any found to lipid abnormalities and to the extent and duration of obesity. Methods: This prospective study was done on 40 obese patients attending to Dr. D. Y. Patil Hospital, Mumbai with complaints of pulmonary functions during the period from January to December 2012. Pulmonary function test was done with the help of Jaegers pneumoscreen. The percentage of body fat was determined by using triceps skin fold thickness technique by using Vernier callipers. Fasting serum samples was collected to analyses cholesterol and triglycerides. Results: Female preponderance was seen in the study (57.5%). Forced expiratory volume, forced vital capacity, maximum mid expiratory flow rate was significantly reduced and the ratio of forced expiratory volume in one second to forced vital capacity was significantly increased in individuals who had abnormal pulmonary function. Decrease in pulmonary function was noted with increased levels of cholesterol and triglyceride but the correlation was not significant. Conclusions: Obese individuals although asymptomatic have significant lung function abnormality in the form of restrictive as well as obstructive pattern. Hence, reduction in the body weight may help in reversal of the pulmonary function indices.